The Role of Small Molecules Containing Fluorine Atoms in Medicine and Imaging Applications - Emily Henary; Stefanie Casa; Tyler L. Dost; Joseph C. Sloop; Maged Henary (Pharmaceuticals, 2024)
The fluorine atom possesses many intrinsic properties that can be beneficial when incorporated into small molecules. These properties include the atom’s size, electronegativity, and ability to block metabolic oxidation sites. Substituents that feature fluorine and fluorine-containing groups are currently prevalent in drugs that lower cholesterol, relieve asthma, and treat anxiety disorders, as well as improve the chemical properties of various medications and imaging agents. The dye scaffolds (fluorescein/rhodamine, coumarin, BODIPY, carbocyanine, and squaraine dyes) reported will address the incorporation of the fluorine atom in the scaffold and the contribution it provides to its application as an imaging agent. It is also important to recognize radiolabeled fluorine atoms used for PET imaging in the early detection of diseases. This review will discuss the many benefits of incorporating fluorine atoms into small molecules and give examples of fluorinated molecules used in the pharmaceutical industry and imaging techniques.